Towards a Generative Approach in Understanding the Kónkóló Timeline in Yoruba Music - Olupemi Oludare (Baltic International Yearbook of Cognition, Logic and Communication, 2023)
The kónkóló timeline is ubiquitous in most Yoruba musical practices; serving as the background rhythmic pattern and time marker, it is the principal pattern that delineates the music’s rhythmic structure. Previous bodies of work have investigated the nature of Western rhythm from a range of different perspectives, such as in terms of cultural significance, cognitive and neural relationships with language and movement, and potential pedagogical and therapeutic value. There is also increasing interest in the connections between formal and traditional semantic approaches to analysing musical meaning, including for rhythmic structures. The current, interdisciplinary study attempts to bring together aspects of these distinct areas of knowledge, through a generative approach, in understanding musical and cultural functions of the kónkóló timeline in Yoruba music. This is attempted by seeking to understand the creative ways in which the kónkóló timeline is used and communicated between the musicians, dancers, and audience in Yoruba music. While this study is based on a generative approach in Yoruba traditional music, which is unlike the generative theories of Western tonal music, it agrees to the presence of a hierarchical system of metrical organization and rhythmic grouping in the music. Data were elicited during fieldwork through observation and interviews of traditional drummers and dancers. The study provided information on the kónkóló timeline’s metric/rhythmic structure as unique inputs, and the predictive outputs in the music, such as specific syllabic and rhythmic generation, movement and dance patterns, and other socio-cultural layers that constitute the full experience of Yoruba music. This also include perspectives on the social and affective features of kónkóló patterns.
Keywords: Generative approach; Kónkóló timeline; Movement; Rhythm; Yoruba music